Pendekatan Case-Based Reasoning (CBR) dalam Pengembangan Sistem Pakar Diagnosis Penyakit Kolesterol : Case-Based Reasoning (CBR) Approach in the Development of an Expert System for Cholesterol Disease Diagnosis - Irmawati Polingala; Azwar; Anas; Jabaluddin Hamud (CV Insight Publisher, 2026)
At present, computers have been widely used in the medical field to assist in diagnosing diseases. One of the most important and frequently encountered diseases is cholesterol-related disease. Cholesterol is a condition that affects many people in Boalemo Regency; however, its treatment is often limited to traditional medicine, and the community tends to be passive regarding the dangers of this condition, resulting in low awareness of their health status. One technique for diagnosing cholesterol-related disease is the use of an expert system. Therefore, this study aims to determine how to design and develop an expert system for diagnosing cholesterol-related disease using the case-based reasoning method, which is capable of performing an initial diagnosis without the direct involvement of an expert or healthcare professional, thereby enabling earlier and more appropriate patient management. The results indicate that the designed cholesterol diagnosis system can be effectively utilized. This is evidenced by testing conducted using the white-box testing method and basis path analysis, which produced a cyclomatic complexity value of V(G) = 5 (CC). In addition, black-box testing demonstrates the correctness of the system logic, indicating that the flowchart logic is valid and that the resulting system is accurate and feasible for use